Ultrafine dual‐phased carbide nanocrystals confined in porous nitrogen‐doped carbon dodecahedrons for efficient hydrogen evolution reaction - Lu, Xue Feng (2020)
Designing novel non-noble electrocatalysts with controlled structures and composition remains a great challenge for efficient hydrogen evolution reaction (HER). Herein, a rational synthesis of ultrafine carbide nanocrystals confined in porous nitrogen-doped carbon dodecahedrons (PNCDs) by annealing functional zeolitic imidazolate framework (ZIF-8) with molybdate or tungstate is reported. By controlling the substitution amount of MO4 units (M = Mo or W) in the ZIF-8 framework, dual-phase carbide nanocrystals confined in PNCDs (denoted as MC-M2 C/PNCDs) can be obtained, which exhibit superior activity toward the HER to the single-phased MC/PNCDs and M2 C/PNCDs. The evenly distributed ultrafine nanocrystals favor the exposure of active sites. PNCDs as the support facilitate charge transfer and protect the nanocrystals from aggregation during the HER process. Moreover, the strong coupling interactions between MC and M2 C provide beneficial sites for both water dissociation and hydrogen desorption. This work highlights a new feasible strategy to explore efficient electrocatalysts via engineering on nanostructure and composition.